Instruction for English Language Learners in the Social Studies Classroom: A Meta-synthesis. Issue 1 (1st March 2016) - Yoder, Paul J.; Kibler, Amanda; van Hover, Stephanie
Abstract : Using the systematic search and coding procedures of a meta-synthesis, this paper reviews the extant literature on English language learners (ELLs) in the social studies classroom. The 15 studies making up the corpus adhere to both topical and methodological criteria. The Language-Content-Task (LCT) Framework informed the coding and analysis of the results. Discussion of the findings provides three primary implications: (1) the need for linguistically and culturally responsive instruction for ELLs in social studies classes, (2) the need for increased training for inservice and preservice social studies teachers in preparation for teaching ELLs, and (3) the need for future research among ELLs in the social studies context.